Skogsforstorelsen fran Adam till Clinton=Deforestation from Adam to Clinton - Persson R. (1998)
The article describes deforestation from early man to our time. During the last 8 000 years forests (very widely defined) may have decreased by about 40%. Deforestation began in West Asia, China, India and the Mediterranean followed by Europe and somewhat later by North America. It has now moved to the tropics at the same time as forest areas are actually increasing in temperate and boreal zones. In a historical perspective forest development can be described as going through several phases. As expected, there was a long phase with little deforestation, then usually a phase or phases with rapid deforestation, a phase of stabilisation and then, in developed countries, an increase in forest area. In Europe, for example, deforestation and recovery has oscillated with for example an increase in forest area during the period of the Black Death. Wars and powerless governments can result in both deforestation and recovery. Rapid deforestation on one period has often been connected to some kind of industry (e.g., mining). Not all forests in the Mediterranean were cleared in classical times as is often described. Forests were left in inaccessible areas and some forests recovered after the decline of the Romans. Much of the deforestation in West Asia and North Africa has taken place in this century.